Assistencialismo Midiático: uma nova estratégia de legitimação social - Pedrinho Guareschi; Giordano Larangeira Dias; Mariane Rigatti Hartmann (Intexto, 2008)
The study is originated from a long investigation about media reception by the population. The five TV programs most attended in the year of 2003, showed by the six most important channels of Brazilian TV, had been investigated, through focus groups. Short videos were produced and showed to thirty groups of discussion, made out of representative people of society. Among the most relevant findings we discuss in the present article only one, considered as central in the research, named “mediatic welfarism”. Such concept shows that the main reason why TV attendants consider a channel, a program or a showman to be a good one, is the fact that he helps people. In the discussion and interpretation of the data, this finding was analyzed having in mind the entire Brazilian history, and the influence of such culture and practices in the construction of a dependent subjectivity, having their roots in welfarist practices present in all the dimensions of society. This practice manifests itself today through a new face: a mediatic welfarism that continues to reproduce relations of domination.